In vitro experimental models of mesothelioma revisited - Singh, Anand; Pruett, Nathanael; Hoang, Chuong D. (Translational Lung Cancer Research; Vol 6, No 3 (June 29, 2017): Translational Lung Cancer Research (Malignant Pleural Mesothelioma: Updates and New Directions), 2017)
Malignant pleural mesothelioma (MPM) is a biologically unusual, highly aggressive cancer that defies current multimodality treatments. Epidemiologic data suggest that this malignancy has not abated despite increasingly strict environmental regulations on asbestos, the putative causative agent for sporadic cases. An incomplete understanding of all the factors mechanistically driving mesothelioma is largely responsible for the current lack of curative treatments. Many approaches have been employed to ascertain the step-by-step molecular events involved in mesothelioma oncogenesis including in vitro, small animal in vivo, and human experimental models; though clearly defined, druggable mechanisms still are elusive. Importantly, the foundation of the latest accepted model of tumor initiation is derived from in vitro systems. A thorough review of in vitro mesothelioma oncogenesis models may suggest further opportunities for discovery.